2012
DOI: 10.1590/s0103-84782012000300008
|View full text |Cite
|
Sign up to set email alerts
|

Estimates of genetic parameters for physic nut traits based in the germplasm two years evaluation

Abstract: In spite of increasingly widespread interest in planting physic nut, breeding efforts are still in its infancy. In that context, an important resource recently established aiming

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

7
20
1
4

Year Published

2012
2012
2021
2021

Publication Types

Select...
7
3

Relationship

4
6

Authors

Journals

citations
Cited by 36 publications
(32 citation statements)
references
References 8 publications
7
20
1
4
Order By: Relevance
“…Estimates of CVe higher than 20% for the productive traits possibly occurred due to the existence of variation within each accession, being similar to those reported in other studies with Jatropha, including this population (Laviola et al, 2010). 2 h estimates obtained for the traits PH12, PH40, CPR40, GY and OY are considered moderate (>50%), and are in accordance with the results reported by Laviola et al (2010Laviola et al ( , 2012b. Peixoto et al (2016), who evaluated productive traits in Jatropha, verified genetic variability between Jatropha accessions of the germplasm bank of EMBRAPA Agroenergy, and in this way, it is possible to obtain gain from selection on these traits.…”
Section: Anova and Estimates Of Genetic Parameterssupporting
confidence: 90%
“…Estimates of CVe higher than 20% for the productive traits possibly occurred due to the existence of variation within each accession, being similar to those reported in other studies with Jatropha, including this population (Laviola et al, 2010). 2 h estimates obtained for the traits PH12, PH40, CPR40, GY and OY are considered moderate (>50%), and are in accordance with the results reported by Laviola et al (2010Laviola et al ( , 2012b. Peixoto et al (2016), who evaluated productive traits in Jatropha, verified genetic variability between Jatropha accessions of the germplasm bank of EMBRAPA Agroenergy, and in this way, it is possible to obtain gain from selection on these traits.…”
Section: Anova and Estimates Of Genetic Parameterssupporting
confidence: 90%
“…In this research, high ȓ gg are reported (> 0.60), according to the classification of Resende (2002), for PH, SD, CPB, and CPR (Table 2), indicating that the progenies maintain relative superiority over the years (at least two measurements for SD). Results for these characteristics at similar magnitudes were also observed by Laviola et al (2012), who evaluated 110 Jatropha genotypes for two years. However, low estimates (< 0.30) were obtained for MHG, NB and GY, which suggests the need for a large number of measurements to achieve a satisfactory determination value.…”
Section: Resultssupporting
confidence: 72%
“…Resultados similares foram obtidos em outros trabalhos com a cultura do pinhão-manso (Laviola et al 2012(Laviola et al , 2014Everson et al 2013;Brasileiro et al 2013;Wani et al 2012).…”
Section: Resultsunclassified